Association of periodontitis with rheumatoid arthritis and atherosclerosis: Novel paradigms in etiopathogeneses and management? - Mena Soory (Dove Medical Press, 2010)
Mena SooryKing’s College London Dental Institute, Denmark Hill, London UKAbstract: There is increasing documentation of a link between inflammatory periodontal disease affecting the supporting structure of teeth, rheumatoid arthritis, and coronary artery disease. Periodontitis is initiated predominantly by Gram-negative bacteria and progresses as a consequence of the host inflammatory response to periodontal pathogens. Lipopolysaccharide, a cell wall constituent stimulates the production of inflammatory cytokines via the activation of signaling pathways perpetuating inflammatory pathogenesis in a cyclical manner in susceptible individuals; with an element of autoimmune stimulation, not dissimilar to the sequential events seen in RA. Periodontitis, also implicated as a risk factor for cardiovascular disease, promotes mechanisms for atherosclerosis by enhancing an imbalance in systemic inflammatory mediators; more direct mechanisms attributed to microbial products are also implicated in both RA and atherogenesis. Severe periodontal disease characterized by clinical and radiographic parameters has been associated with ischemic stroke risk, significant levels of C-reactive protein and serum amyloid A, amongst others common to both periodontitis and atherosclerosis. Existing data supports the hypothesis that persistent localized infection in periodontitis may influence systemic levels of inflammatory markers and pose a risk for RA and atherosclerosis. A common nucleus of activity in their pathogeneses provides novel paradigms of therapeutic targeting for reciprocal benefit.Keywords: periodontitis, RA, atherosclerosis, periodontal pathogens, cytokines, therapeutic targets